2018
DOI: 10.1002/ejp.1313
|View full text |Cite
|
Sign up to set email alerts
|

Outcome domains and pain outcome measures in randomized controlled trials of interventions for postoperative pain in children and adolescents

Abstract: Recommended core outcomes have been insufficiently used in randomized controlled trials about postoperative pain in children, which hinders comparability of studies and makes synthesis of evidence difficult.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 14 publications
(24 reference statements)
2
19
0
1
Order By: Relevance
“…Several studies compared the use of the outcomes that the COS recommended before and after the publication of the COS [17,19,29]. Only one of these studies, which assessed a COS for ankylosing spondylitis, noted some increase in uptake of the full COS after publication (0% RCTs before versus 20% RCTs after).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies compared the use of the outcomes that the COS recommended before and after the publication of the COS [17,19,29]. Only one of these studies, which assessed a COS for ankylosing spondylitis, noted some increase in uptake of the full COS after publication (0% RCTs before versus 20% RCTs after).…”
Section: Discussionmentioning
confidence: 99%
“…They extracted data about the outcomes included from the RCT reports and SRs. Two (8%) studies searched SRs to identify RCTs [28,29], and one (4%) study included RCTs identified from one systematic review [30]. Five (19%) studies identified RCTs by searching in a clinical trials registry [31e35].…”
Section: Methods Used To Assess Uptakementioning
confidence: 99%
See 1 more Smart Citation
“…In a study of 337 trials, which analyzed outcome domains and pain outcome measures in randomized controlled trials (RCTs) of interventions for treatment of postoperative pain in children and adolescents and compared them with recommendations of the PedIMMPACT, it was found that the median number of outcomes reported in RCTs was 2 for PedIMMPACT outcomes (range, 0 to 6) (7).…”
Section: Adherence To Cos and Coms In Clinical Trialsmentioning
confidence: 99%
“…36,56 Consistent with the biopsychosocial model, 18 a more comprehensive assessment of pain has been recommended, 38 including pain intensity, satisfaction and treatment response, side effects, pain interference, emotional response, and economic factors. However, pediatric pain research rarely includes all recommended domains of pain assessment, 7 possibly due to the lack of validated, comprehensive measures. Several multidimensional measures of pediatric pain have been developed, but only 4 have been found to have adequate psychometric properties.…”
mentioning
confidence: 99%